2017
DOI: 10.1111/jfs.12421
|View full text |Cite
|
Sign up to set email alerts
|

Chicken fillets subjected to UV‐C and pulsed UV light: Reduction of pathogenic and spoilage bacteria, and changes in sensory quality

Abstract: We have compared the efficacy of continuous ultraviolet (UV‐C) (254 nm) and pulsed UV light in reducing the viability of Salmonella Enteritidis, Listeria monocytogenes, Staphylococcus aureus, enterohemorrhagic Escherichia coli, Pseudomonas spp., Brochothrix thermospacta, Carnobacterium divergens, and extended‐spectrum β‐lactamase producing E. coli inoculated on chicken fillet surface. Fluences from 0.05 to 3.0 J/cm2 (10 mW/cm2, from 5 to 300 s) used for UV‐C light resulted in average reductions from 1.1 to 2.8… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
49
2
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 72 publications
(67 citation statements)
references
References 76 publications
5
49
2
1
Order By: Relevance
“…Previous in vitro experiments also confirmed the reduction (5–7 log cfu/g) of several Salmonella strains ( Salmonella Typhimurium, Salmonella Enteretidis) by different UV‐C doses, corroborating with our results (Allende, McEvoy, Luo, Artés, & Wang, ; Escalona, Aguayo, Martínez‐Hernández, & Artés, ; McLeod et al, ). On the other hand, only few studies have focused on the effect of the UV‐C radiation on reduction of Salmonella spp.…”
Section: Resultssupporting
confidence: 92%
See 1 more Smart Citation
“…Previous in vitro experiments also confirmed the reduction (5–7 log cfu/g) of several Salmonella strains ( Salmonella Typhimurium, Salmonella Enteretidis) by different UV‐C doses, corroborating with our results (Allende, McEvoy, Luo, Artés, & Wang, ; Escalona, Aguayo, Martínez‐Hernández, & Artés, ; McLeod et al, ). On the other hand, only few studies have focused on the effect of the UV‐C radiation on reduction of Salmonella spp.…”
Section: Resultssupporting
confidence: 92%
“…The total color difference in caiman meat treated with 0.010, 0.016, 0.037, 0.065, 0.105, 0.127, and 0.199 J/cm 2 was higher than 5 units, indicating that the UV-C application at these doses resulted in perceived color changes by visual observation (Tazrart, Zaidi, Lamacchia, & Haros, 2016). Although this fact indicates instrumental color changes perceptible to consumers, previous sensory studies reported no color changes in chicken meat, which has a similar visual color to caiman meat, treated with UV-C doses higher than those used in the present study (McLeod et al, 2018;Park & Ha, 2015).…”
Section: Resultscontrasting
confidence: 57%
“…Research on sanitization in fish factories has been carried out to optimize treatments and increase effectivity. According to Holck et al [ 149 ] and Mcleod et al [ 150 ], UV light could be an alternative for surface decontamination given that it causes microbial inactivation through DNA damage. Chlorine and the products that produce chlorine include hydrogen peroxide and quaternary ammonium compound, two of the disinfectants commonly used in seafood plants [ 151 , 152 ].…”
Section: Control Strategies Implemented In the Food Industrymentioning
confidence: 99%
“…At 1.27 J cm −2 PUVL, E. coli on lean surface chicken thighs was reduced by 1.22 and 2.02 log 10 CFU cm −2 , whereas PUVL treatment on skin surface thighs resulted in 1.19 and 1.96 log 10 CFU cm −2 reductions with 5 and 45 s treatments, respectively (Cassar et al ., 2019). Treatments with 1.25 to 18.0 J cm −2 PUVL against E. coli resulted in reductions of 0.9 to 3.0 log 10 CFU cm −2 on chicken fillets (McLeod et al ., 2018). Rajkovic et al .…”
Section: Introductionmentioning
confidence: 99%